Wilma Mankiller - Sorell, Traci (She persisted (Philomel Books), 2022)
The descendant of Cherokee ancestors who had been forced to walk the Trail of Tears, Wilma Mankiller experienced her own forced removal from the land she grew up on as a child. As she got older and learned more about the injustices her people had faced, she dedicated her life to instilling pride in Native heritage and reclaiming Native rights. She went on to become the first woman Principal Chief of the Cherokee Nation.